OPERATOR SELF ADJOINT PADA RUANG HILBERT - Gunawan, Gunawan (UJMC (Unisda Journal of Mathematics and Computer Science), 2018)
In this article, will discuss definition, examples, algebra properties, and some characteristic of self-adjoint operators on Hilbert space. In the Hilbert space there are types of bounded linear operators such as adjoint operators and self-adjoint operators. To investigate characteristic of self-adjoint operator required concepts of Hilbert space, operators on Hilbert spaces, Riesz representation theorem, and adjoint operators on Hilbert space. It then takes a thought to investigate the characteristic of self-adjoint operators. Discussion of self-adjoint operators more emphasis on understanding the definition, algebra properties, and characteristic of self-adjoint operators on Hilbert space. The results obtained are algebra properties of self-adjoint operators such as addition, subtraction, scalar multiplication, and multiplication of self-adjoint operators. In addition, some characteristic associated with self-adjoint operators on Hilbert space.